The David procedure after the Ross operation: case series - I. I. Chernov; S. T. Enginoev; D. A. Kondrat'ev; A. A. Zenkov; A. A. Abdurakhmanov; D. G. Tarasov (Российский кардиологический журнал, 2022)
Pulmonary autograft in the aortic position provides high survival rate and quality of life for patients, low incidence of valve-related complications, and excellent hemodynamic characteristics both in the early and long-term period. However, in some patients in the long-term period, pulmonary autograft may dilate, which in turn is one of the reasons for reoperations. In patients who require surgery for annuloaortic ectasia with aortic valve (AV) regurgitation or aortic root aneurysm (or both) with normal AV leaflets, David procedure is considered.Aim. To analyze results of David procedure after a prior Ross operation.Material and methods. From April 2009 to December 2020, 212 Ross operations were performed on patients 18 years of age and older. The median age of the operated patients was 34 (27-45) years. In the long-term period, 10 (4,7%) patients required a second AV operation and 7 (3,3%) of them required another intervention on the ascending aorta due to aortic dilatation. Four out of 10 patients underwent David procedure. The follow-up period for patients after David procedure ranged from 2 to 84 months.Results. The age of patients ranged from 23 to 45 years. Three patients had hypertension. The follow-up period from Ross's operation to David's one was 26 to 140 months. All patients had enlarged aortic annulus from 27 to 30 mm. The duration of myocardial ischemia ranged from 87 to 142 minutes, while the duration of artificial circulation — from 119 to 165 minutes. The graft diameter was 30 mm in two patients and 32 mm in the remaining ones. The length of stay in intensive care unit ranged from 16 to 23 hours. In the early postoperative period, no one had following postoperative complications: acute renal failure requiring hemodialysis, perioperative myocardial injury, stroke, sternal infection, respiratory failure requiring mechanical ventilation for ≥24 hours, resternotomy for bleeding and tamponade. In addition, there were no in hospital deaths. All patients had no aortic regurgitation at the time of discharge. All patients are alive and there were no reoperations. In one patient, in the long-term period, there was a mild aortic regurgitation, while in three patients — there is no regurgitation.Conclusion. The presented case series show that David procedure can be performed safely and effectively in a significant number of patients requiring a second autograft surgery due to neosinus dilatation. In the medium term, the David procedure has shown good outcomes in these patients with 100% survival and no aortic regurgitation and reoperation.